PENGARUH PROFITABILITAS LEVERAGE LIKUIDITAS DAN UKURAN PERUSAHAAN TERHADAP FINANCIAL DISTRESS PADA SUB SEKTOR PROPERTY & REAL ESTATE: EFFECT OF PROFITABILITY LEVERAGE LIQUIDITY AND COMPANY SIZE ON FINANCIAL DISTRESS IN THE PROPERTY & REAL ESTATE SUB-SECTOR - Handayani, Fice; Yusran, Gita Amalia (Sekolah Tinggi Ilmu Ekonomi Balikpapan, 2024)
The aim of this research is to determine and analyze the influence of ROA, DAR, CR, and company size on financial distress in the property and real estate sub-sector on the Indonesia Stock Exchange for the 2018-2022 period. Purposive sampling methods is used for sampling techniques. Multiple Linear Regression is used for data processing and analysis. So the results obtained are: return on assets has a positive and significant influence, debt to assets ratio has a negative and significant influence, current ratio has a positive and significant influence, company size does not have a negative and significant influence. ROA, DAR, CR, and company size simultaneously and significantly influence financial distress.